Animal Models of Peripheral Pain: Biology Review and Application for Drug Discovery. (January 2020) - Kaliyaperumal, Saravanan; Wilson, Kristin; Aeffner, Famke; Dean, Charles
Pain is a complex constellation of cognitive, unpleasant sensory, and emotional experiences that primarily serves as a survival mechanism. Pain arises in the peripheral nervous system and pain signals synapse with nerve tracts extending into the central nervous system. Several different schemes are used to classify pain, including the underlying mechanism, tissues primarily affected, and time-course. Numerous animal models of pain, which should be employed with appropriate Institutional Animal Care and Use approvals, have been developed to elucidate pathophysiology mechanisms and aid in identification of novel therapeutic targets. The variety of available models underscores the observations that pain phenotypes are driven by several distinct mechanisms. Pain outcome measurement encompasses both reflexive (responses to heat, cold, mechanical and electrical stimuli) and nonreflexive (spontaneous pain responses to stimuli) behaviors. However, the question of translatability to human pain conditions and potential treatment outcomes remains a topic of continued scrutiny. In this review we discuss the different types of pain and their mechanisms and pathways, available rodent pain models with an emphasis on type of pain stimulations and pain outcome measures and discuss the role of pathologists in assessing and validating pain models.